Belajar Asyik Dengan Kaligrafi: Mengasah Minat Keterampilan Menulis Bahasa Arab - M. Taufik; Sri Aisyah; Abdullah Khusairi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Discussing calligraphy as an Islamic artwork is very interesting because it displays the beauty and meaning of each stroke of the letters, especially in the Qur'an. Calligraphy is a visual and correspondence skill. It also helps to learn and understand the Arabic language. Arabic is essential to the teaching of Islam as it serves as a way to convey strictly and paves the way for Islamic history and scholarly works. The subjective differentiation strategy was used in this study to examine the relationship between the excellence of students in Arabic language education at Imam Bonjol State Islamic University Padang West Sumatra and their ability to compose Arabic and calligraphy as an improvement in learning, which allows them to concentrate on culture and expression related to Arabic. The consequences of this study indicate that interest in calligraphy as a whole has an impact on students' Arabic composing ability and aptitude. Students who have both interests and abilities will generally get greater help from others, but students who are basically interested need greater help. This study shows how important calligraphy is to further develop Arabic composing ability and demonstrates the work of the contrasting supporting elements of interest and ability.